2022
DOI: 10.1017/s0031182022000075
|View full text |Cite
|
Sign up to set email alerts
|

Tissue eosinophilia correlates with mice susceptibility, granuloma formation and damage during Toxocara canis infection

Abstract: An increase in peripheral blood eosinophils in helminth infections is expected, and these cells are known to promote immunity against these parasites. However, studies have suggested that in some specific helminths, eosinophils may promote the needs and longevity of these parasites, and their role in these infections remains undefined, including in Toxocara canis infection. Thus, this study aimed to investigate the role of eosinophils in the context of larval migration of T. canis and the immunopathological as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…Resende et al (13) demonstrated that in toxocariasis, there is a mixture of Th2 and Th17 inflammatory responses, observed by the increase of the cytokines IL-4, IL-5, IL-13, IL-6, and IL-17 in the serum of mice, during the phase of larval migration, showing that T. canis larvae are capable of triggering IL-17 production. Previous studies by our group also observed that the IL-33/ST2 pathway in mice infected with T. canis increased hepatic and brain parasite load and reduced IL-17 activity (14). In our study, the presence of IL-17RA appears to be relevant to reduce the parasite load in the acute phase of infection in the lungs, and this control in the initial phase is essential to prevent a greater number of larvae from migrating to more susceptible organs, such as the brain.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Resende et al (13) demonstrated that in toxocariasis, there is a mixture of Th2 and Th17 inflammatory responses, observed by the increase of the cytokines IL-4, IL-5, IL-13, IL-6, and IL-17 in the serum of mice, during the phase of larval migration, showing that T. canis larvae are capable of triggering IL-17 production. Previous studies by our group also observed that the IL-33/ST2 pathway in mice infected with T. canis increased hepatic and brain parasite load and reduced IL-17 activity (14). In our study, the presence of IL-17RA appears to be relevant to reduce the parasite load in the acute phase of infection in the lungs, and this control in the initial phase is essential to prevent a greater number of larvae from migrating to more susceptible organs, such as the brain.…”
Section: Discussionsupporting
confidence: 71%
“…In toxocariasis, the immune response triggered during infection is associated with eosinophilia in peripheral blood, eosinophilic infiltration around larval migration sites, and a production of type 2 (Th2) T helper immune response (20). Recent studies demonstrate that several cytokines are present during the acute and chronic phases of the disease, and among them is IL-17, which is increased during infection (13,14). In this way, the study of the role of the IL-17 pathway in toxocariasis becomes essential to expand the immunological knowledge about the disease and provide avenues for the development of drugs and therapeutic targets that can prevent larval migration in accidental hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed an increase in the parasite load in the lungs of IL-17RA mice at 3dpi. In a previous study, a change in larval load was also observed with 3dpi in the lungs in GATA1 -/- mice infected with T. canis compared to WT ( 23 ). Although parasite migration is erratic, at 3dpi is the peak of larval migration in the lung ( 13 ), thus we found a greater number of larvae at this time of infection, which may have shown greater statistical differences between the groups.…”
Section: Discussionmentioning
confidence: 65%
“…Samples were acquired in LSR Fortessa (BD Biosciences, USA) and analyzed with FlowJo software (Tree Star, Ashland, OR). Data analysis was followed by dimensionality reduction and visualization by t-Distributed Stochastic Neighbor Embedding (tSNE) using Cytofkit ( 23 ) and rPhenograph to group cells into clusters according to their similarity of activation/expression molecules and cytokines and rPhenograph to group cells into clusters according to their similarity of activation/expression molecules and cytokines. Each experimental group in tSNE analysis represent 6 mice with input of the same number of cells.…”
Section: Methodsmentioning
confidence: 99%